Procurement of healthy lunch for adolescents to prevent iron deficiency anemia (IDA) in Prambanan school area - FItriana Sundari (BKM Public Health and Community Medicine, 2021)
Objective: This study aim to reduce the rate of iron deficiency anemia in adolescents in the Prambanan area. People still thingking the symptoms of IDA are not serious and have a long-term impact. Iron Deficiency Anemia (IDA) has an impact on cognitive decline in adolescent girls (Hb <12 mg / dL), this condition causes their productivity to decline both in school and in the work area. By the time they grow up, it can cause a high risk of pregnancy and delivery LBW’s baby. The government still focuses on curative treatment rather than promotion or prevention. The highest ADB rate in Sleman district is in Prambanan subdistrict. Content : First, regulation about the day to drink bloods plus tablets was unaffective to decrease IDA in some areas. Second, according to article review of Sekiyama that the provision of lunch can increase consumption of animal protein and also increase hemoglobin and hematocrit levels in children which this article containing the similar program and become the foundation of this study. Beside of that provide this program also include campaign with a booklet containing a healthy breakfast and dinner’s menu as a source of knowledge for adolscents and their parents. Third, canteen should be renovation to provide properly kitchen and dining area than empower the canteen workers who have been selling fried snack, instant noodles or other unhealthy foods to cook healthy and nutritious food in canteen for student lunches. Fourth, the regulatory system is decentralized according to the nature of the region. Funding sorces can come from Corporate Social Responsibility (CSR), government subsidies and a funding system from wealthy parents of students. Conclusion: procurenment of healthy lunch and campaign use booklet will accepted by stakeholder because can decrease IDA in adolescents without causing conflict from food vendors around the school.